Playing the physicist / loving the bomb an analysis of dramatic representations of the atomic physicists in three plays - Or, Mary Elizabeth Dano; Villareal, Corazon D. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2015)
This thesis examines three plays - In the matter of J. Robert Oppenheimer (964) by Heinar Kipphardt, The Physicists (1964) by Friedrich Durrenmatt and Copenhagen (1998) by Michael Frayn - as sites of memory of the atomic bomb. It analyzes how the material, symbolic and functional aspets of each fulfill and at times refute Pierre Nora's characterization of lieux de memoire. The materiality of the stage, dramatic script and the historical documents used as sources for the script are spaces in which memory and rememoration of the atomic physicists is engaged again and again. Dramatic elements within the plays-along with the plays themselves-are symbols of the memory of the atomic bomb, which is always necessarily a negotiation between guilt for and justification of its existence. The plays thus utilized the subject position of the atomic physicists and the settings in which they are placed as symbols of this negotiation. These significations are analyzed through dialogue and narrative arc. The functional asect of these plays as lieux de memoire lies in their capacity not only to preserve but to mobilize memory of the atomic bomb. Through their fuctionality with those who engage them-reader, writer, actor, producer-memory of the atomic bomb is transmitted and transformed and always, therefore, kept alive.
Thesis (B.A. in Comparative Literature)
Includes bibliographical references and appendices
Keywords: Atomic bomb in literature; Episodic memory